RELATIONSHIP BETWEEN BLOOD PRESSURE WITH GLOMERULAR FILTRATION RATE (GFR) IN PATIENTS WITH CHRONIC RENAL FAILURE - Ailsa Dzakiyah Dzahabiyah Hibatulloh (Ailsa Dzakiyah Dzahabiyah Hibatulloh, Fiora Ladesvita, 2023)
The prevalence of hypertension and chronic kidney disease continues to increase worldwide and has the potential to experience more significant cardiovascular disease. Older patients have also reported an association between a modest decrease in glomerular filtration rate (GFR) and an increase in systolic blood pressure. As the prevalence of chronic kidney disease (CKD) increases with age, multiple complications can occur, including hypertension, diabetes, and other cardiovascular diseases. Multimorbidity is defined as the condition of having two or more chronic morbidities. This study aims to evaluate the relationship between blood pressure and multimorbidity with the glomerular filtration rate (GFR) of chronic renal failure patients at RST Dompet Dhuafa Parung, Bogor. This research is retrospective research with the Consecutive Sampling method. Data was taken through a medical record in 112 samples of chronic renal failure patients undergoing hemodialysis from January 2021 to March 2022. The results of the Spearman correlation test showed a p-value 0.025 in the relationship between systolic blood pressure and GFR and a p-value 0.008 in the relationship between blood pressure diastolic with GFR. At the same time, the results of Kendall's Tau_B correlation test showed a p-value 0.212 in the relationship between the number of comorbidities and GFR. It can be seen that there is a relationship between systolic blood pressure and diastolic blood pressure, and GFR. Whereas, there is no relationship between the numbert of comorbidities and GFR in chronic renal failure patients in RST Dompet Dhuafa Parung Bogor.